2017
DOI: 10.1017/aae.2017.16
|View full text |Cite
|
Sign up to set email alerts
|

Bankers’ Forecasts of Farmland Values: A Qualitative and Quantitative Evaluation

Abstract: Abstract. This study evaluates the farmland price forecasts provided by the Federal Reserve Bank of Chicago's Land Values and Credit Conditions Survey from 1991: quarter 1 (Q1) through 2016: Q1. Prior studies have demonstrated that similar surveys of agricultural bankers provide accurate predictions of the direction of future farm real estate values through qualitative forecast evaluation. This study extends the existing knowledge base by converting the qualitative responses to quantitative expectations. The q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Zakrzewicz et al (2013) discovered that expert reviews may improve the accuracy of price forecasts. Kuethe and Hubbs (2017), however, found that the experts' forecasts which they analysed were unbiased but inefficient, so that the aggregate forecast error was correlated with past aggregate forecast errors. This shows that expert knowledge does not outperform other methods, but statistical models are also needed.…”
Section: Introductionmentioning
confidence: 99%
“…Zakrzewicz et al (2013) discovered that expert reviews may improve the accuracy of price forecasts. Kuethe and Hubbs (2017), however, found that the experts' forecasts which they analysed were unbiased but inefficient, so that the aggregate forecast error was correlated with past aggregate forecast errors. This shows that expert knowledge does not outperform other methods, but statistical models are also needed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the study suggests that farmland purchasers do not make efficient use of all available information when forming expectations of future returns. Kuethe and Hubbs (2017) conduct a more direct test of rational expectations by examining quarterly farmland price expectations of agricultural bankers collected through the Federal Reserve Bank of Chicago's Land Values and Credit Conditions Survey between 1991Q1 -2016Q1. Using survey quantification methods on aggregated survey responses, the authors also reject rational expectations.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Kuethe and Oppedahl (2020) extend the work of Kuethe and Hubbs (2017) by examining an unbalanced panel of individual responses to the Federal Reserve Bank of Chicago's Land Values and Credit Conditions Survey between 1993Q1-2019Q2. Kuethe and Oppedahl (2020) similarly reject rational expectations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations